The moral conscience from a neuroethcal Standpoint. From Darwin to Kant - Cortina, Adela (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
The personal moral conscience is one of the keystones of moral life. Darwin went as far as to claim that this constitutes the most important difference between man and the lower animals. Yet the most relevant philosophical proposals of our times (Rawls, Habermas) do not expressly deal with this, perhaps because, as Aranguren said, they gave priority to intersubjective ethics over intrasubjective ethics. Without reconstructing that intrasubjective ethics, however, both personal and social life is watered down. In this work an attempt is made to explain what personal moral conscience consists of, what its neurobiological foundations are, and whether these are enough to explain its irreplaceable role in moral life. To answer these questions we will have to go from Darwin to Kant.